Distribution Incidence of Herniated Nucleus Pulposus in RSPAD Gatot Soebroto - Evan, Evan; Yonathan, Christian; Kristianto, Yusak; Agoestino, Agoestino; Marta, Grace (Jurnal MedScientiae, 2022)
Low back pain (NPB) is one of the most common disease complained by all people with a prevalenceof 12-35% in which 10% of them will develop into chronic results from back pain. One of the causesthat require follow-up is a herniated nucleus pulposus (HNP). HNP is the most common spinaldegeneration disease and causes 30% to 80% of NPB cases. Magnetic resonance imaging (MRI) is the best screening modality for assessing disc morphology and diagnosing HNP. This study aims to look for distribution incidence of herniatednucleus pulposus in RSPAD Gatot Soebroto in the January 2017-January 2018 period. This studyused a cross sectional research design with a total sampling technique, 73 samples were obtained.Analysis of the data used in this study is univariate analysis. The results of this study found that therewere 73 patients diagnosed HNP with MRI, more dominated by male patients as many as 39 patients(53.4%). The highest age experienced by HNP is age 61-70 years as many as 18 patients (24.7%). For the highest work of HNP are Military as many as 15 patients (20.5%). There was no history oftrauma that caused HNP in this study. Based on the degree of the HNP protrusion level of 37 patients(50.7%). The most HNP locations are in the lumbar area as much as 61 people (67.8%)